Raising Environmental Awareness among Students of SDN 4 Tebing Tinggi in Flood Disaster Mitigation Efforts: Meningkatkan Kesadaran Peduli Lingkungan Pada Siswa-Siswi SDN 4 Tebing Tinggi Dalam Upaya Mitigasi Bencana Banjir - Sispa Pebrian (Institute of Educational, Research, and Community Service, 2023)
Flooding is a natural disaster that cannot be prevented once it comes. Flood disasters often occur in several areas of Kuantan Singi district, including Benai sub-district, Tebing Tinggi village. There are many phenomena that cause flooding in high cliff villages, namely river conditions that are increasingly narrow, large piles of rubbish, and roads with potholes that are badly damaged. In this incident, researchers are very motivated to find out what government and local communities can do to seek flood disaster mitigation activities in Tebing Tinggi. The method used by Tebing Tinggi Village Kukerta Students in implementing this activity is making rubbish bins which have been collected into 2 types, namely Organic and Non-organic, providing an education to students at SDN 004 Tebing Tinggi, and collecting rubbish around the school and throwing it into the rubbish bin which has been given by Kukerta Students to the school. This activity was carried out by students as a form of concern for the flood disaster that occurred in the village in 2019. And we hope that holding this activity can reduce the risk of disasters in the future, and determine priorities and find solutions in dealing with flood disasters